Postoperative results of minimally invasive direct coronary artery bypass procedure in 234 patients - Monsefi, Nadejda; Alaj, Eissa; Sirat, Sami; Bakhtiary, Farhad (Frontiers in Cardiovascular Medicine, 2023)
Introduction Minimally invasive approach in cardiac surgery has gained popularity. In order to reduce surgical trauma in coronary surgery minimally invasive direct coronary artery bypass (MIDCAB) has already been established. This technique has been introduced for revascularisation of isolated left anterior descending (LAD). It can also be performed for hybrid revascularisation procedure in multi-vessel disease. Methods From 2017 to 2021, 234 patients received MIDCAB operation in our heartcenter 73% were male. Most of the patients had two or three vessel disease (74%). The average age of the patients was 66 ± 12 years mean. The left internal mammary artery (LIMA) was anastomosed to the LAD through left minithoracotomy approach. Multi-vessel MIDCAB (MV-MIDCAB) including two anastomoses (T-graft to LIMA with additional saphenous vein graft) was done in 15% (n = 35). Results The average operation time was 2.3 ± 0.8 h mean. The 30-day mortality was 1.7% (n = 4). The average amount of packed red blood cells (pRBC) that was given intra- and postoperatively was 0.4 ± 0.8 units mean. The mean intensive care unit stay (ICU) was 1 ± 1.2 days. Three patients (1.3%) had wound infection postoperatively. The rate of neurologic complications was 0.4% (n = 1). Two patients (0.9%) had myocardial infarction and received coronary re-angiography perioperatively including stent implantation of the right coronary artery. Discussion The MIDCAB procedure is a safe and less traumatic procedure for selected patients with proximal LAD lesions. It is also an option for hybrid procedure in multi-vessel disease. The ICU stay and application of pRBC’s are low. Our MIDCAB results show a good postoperative clinical outcome. However, follow-up data are necessary to evaluate long-term outcome.